Tanzania Public Expenditure Review : National Agricultural Input Voucher Scheme - World Bank (Washington, DC, 2014)
Tanzania is largely an agriculture-based economy. This sector accounts for over three-quarters of national employment, and approximately 25 percent of gross domestic product (GDP). The national agricultural input voucher scheme (NAIVS) is a market smart input subsidy program designed in response to the sharp rise in global grain and fertilizer prices in 2007 and 2008. The main aim of the program is to raise maize and rice production, and thus preserve Tanzania's household and national food security. During the period from 2008 to 2013, approximately United States (U.S.) 300 million dollars has been invested in providing more than 2.5 million smallholder farmers with a 50 percent subsidy on a one acre package of maize or rice seed, and chemical fertilizer. The input subsidy program helped Tanzanian smallholders harvest more than 2.5 million tons of additional maize and rice grain. The NAIVS program also faced multiple logistical challenges. These challenges are being considered in the government's new big results now initiative. This report summarizes the results of an overview of the program, and the results of two major impact surveys independently conducted in late 2010 and late 2012. Chapter one places the NAIVS in context, reviewing the status of the agricultural economy and the importance of grain production in the country. Chapter two provides an overview of the NAIVS program, including budget, expenditure, and implementation rules. Chapter three briefly summarizes the impact survey results and highlights the financial and economic returns of the program. Chapter four discusses the challenges faced during implementation of the NAIVs, and chapter five reviews the implications for further investment in this sort of input subsidy.